Management of chicken pox ulcer manifestation in an 8-years-old patient: Penatalaksanaan manifestasi ulkus akibat cacar air pada pasien berusia 8 tahun - Sulistyani; Sri Hernawati (Makassar Dental Journal, 2020)
Background: Chicken pox is the primary acute infectious disease caused by the Varicella-Zoster Virus (VZV) which attacks skin and mucosa accompanied by polymorphic skin disorders, mainly located in the central part of the body. Case: an 8- years-old woman came to the Dental Hospital, Jember University complaining about pain felt on the upper lip when used for eating for 7 days. The patient also had a fever and fluid-filled lumps appear in both hands and back since about 6 days ago. Clinical overview of the upper lip show erosion, irregular shape, clear borders, red, moist lesions, rough surfaces and pain. In both hands there are lesions in the formof erosion,the base is red,moist and the boundaryis clear. Management: Therapy applied to patients i.e. Aloclair gel as a topical analgesic medicine and moisturizer, Acyclovir tablet as an antiviral agent, paracetamol syrup as an antipyretic and multivitamin B complex as supporting therapy. Discussion: Chicken pox is a disease that can heal itself, but to speed up healing process and to reduce discomfort due to the symptoms that appear, causative and supportive cares are necessary. Conclusions: Management of a chicken pox patient aged 8 years old is conducted by providing Aloclair oral gel, Acyclovir tablets, paracetamol syrup and multivitamin of vitamin B complex and zinc to support healing process, and instruct the patient to avoid direct contact with other people.